LA REMILITARIZACIÓN DE AMERICA LATINA - Salazar Pérez, Robinson (La Sociología en sus Escenarios, 2009)
Abstract. The plans established in Latin America, instead of eradicating the drug traffic, have two clear objectives: to create the propitious conditions to privatize the resources public related to the water, the energy and biological route; to increase the paramilitaries to guard the future investments and to create programs of social cleaning to eliminate the possibility of protests in the region. Resumen. Los planes establecidos en América Latina, en lugar de erradicar el narcotráfico, tienen dos objetivos claros: crear las condiciones propicias para privatizar los recursos públicos relacionados con el agua, la energía y la ruta biológica; y aumentar los paramilitares para proteger las futuras inversiones, crear programas de limpieza social y para eliminar la posibilidad de protestas en la región.